Essential Trace Minerals for Grazing Cattle in Florida - John D. Arthington (EDIS)
Revised! AN086, an 8-page fact sheet by John D. Arthington, reviews trace minerals that are recognized as deficient in Florida grazing cattle and that are important considerations in supplementation programs, supplementation, and analysis of herd trace mineral status. Published by the UF Department of Animal Science, May 2008.